Citraan Puisi Anak Majalah Bobo Edisi 40—45 Tahun 2016 - Fadhilatun Hayatunnufus (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2018)
This research entitled "The Imagery in a Collection of Child Poems in Bobo Magazines in 2016." The formulation of the problem in this study is what types of imagery contained in the poetry of children published in Bobo magazine. The purpose of this study is to describe any kinds of imagery contained in the poetry of children in Bobo magazine. The type of this research is a qualitative research. The technique which was used in data collection is a literature study from 15 poems. To analyse the data, the researcher used a descriptive analytic method which is done by describing facts and analyzing it. The results of this study indicate that the imagery contained in the poetry of children in Bobo magazine is visual imagery, kinestethic imagery , smell imagery, taste imagery , and tactile imagery. The most dominant image used by children in making poetry in Bobo magazine is visual imagery.